Risk Analysis of Work Accidents at CV. Sumber Rejeki Gresik with Failure Mode and Effect Analysis (FMEA) and Root Cause Analysis (RCA) Methods - Amrillah, Mohammad Suhud; Rizqi, Akhmad Wasiur; Jufriyanto, Moh. (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
In the current industrial era, Occupational Safety and Health (OHS) is something that needs to be considered. Increasing awareness of OHS in every employee will have a very good impact both in terms of material and non-material. If this is ignored, it will be fatal and of course can cause losses. The accident data totaled 6 times which was calculated from January 2022 to November 2022 with a total of 9 employees. The number of accidents that occurred is still said to be very high with a percentage of 54% of the total workforce. this is not the same as government policies that implement zero accidents in work accidents. on CV. Sumber Rejeki has 9 types of OHS Risk. It is different from the government's policy of implementing zero accidents in OHS. CV. Sumber Rejeki has 9 types of OHS risks. This study uses the Failure Mode and Effect Analysis (FMEA) method. after risk identification, improvements are proposed with Root Cause Analysis (RCA) to find out the root of the problem. That workers' awareness of the use of PPE is lacking, such as the result of the RPN value reaching 3 for the three highest events. So it is proposed to follow the guidelines for work standards and pre-work checks. Di era Industri saat ini, Keselamatan dan Kesehatan Kerja (K3) merupakan hal yang perlu diperhatikan. Peningkatan kesadaran akan K3 pada setiap karyawan akan memberikan dampak sangat baik dari segi materi maupun non materi. Jika hal ini diabaikan, maka akan berakibat fatal dan tentunya dapat menimbulkan kerugian. Data kecelakaan berjumlah 6 kali yang dihitung dari bulan Januari 2022 sampai November 2022 dengan jumlah 9 karyawan. Kecelakaan yang terjadi masih dikatakan sangat tinggi dengan persentase 54% dari total tenaga kerja. Berbeda dengan kebijakan pemerintah yang menerapkan zero accident pada k3. CV. Sumber Rejeki memiliki 9 jenis risiko K3. Penelitian ini menggunakan metode Failure Mode and Effect Analysis (FMEA). setelah identifikasi risiko, diusulkan perbaikan dengan Root Cause Analysis (RCA) untuk mengetahui akar permasalahan. Kesadaran pekerja terhadap penggunaan APD kurang, seperti hasil dari nilai RPN mencapai 3 untuk tiga kejadian tertinggi Sehingga diusulkan untuk mengikuti panduan standart kerja dan pengecekan sebelum kerja.